ANTESEDEN DAN KONSEKUENSI DARI KUALITAS HUBUNGAN - Ali Faik (Jurnal Manajemen dan Pemasaran Jasa, 2012)
This antecedents and consequences research is from relationship quality aimedto analyze the use of relationship quality dimensions such as customer orientation,relational orientation, mutual disclosure and service providers attribute, that are will impact to share of purchase, relationship continuity dan word of mouth in certain service industry like restaurant. The method of this reasearch is convenience sampling by givingquestionnaires to D’Cost costumers in Gondangdia region, South Jakarta within one month with 185 respondents. The result of this emperical research is relationship quality in service industry D’Cost showed customer orientation has significant influence to relationsip quality, relational orientation has significant influence to relationship quality, mutual disclosure has significant influence to relationship quality, service providers attributes has significant influence to relationship quality. Whereas, relationship quality has significantinfluence to share of purchase, and relationship quality has influence to relationship quality mwhich influence word of mouth.Keywords : relationship quality, relational orientation, customer orientation, mutual disclosure, service providers, share of purchase, word of